White Onion (Allium sativum) Extract as a Vegetable Larvicide in Blowfly (Calliphoridae) Control (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2019)
One way to control blowflies is by using chemical pesticides; however, it causes negative effect to human, environment, and other organisms. One alternative effort is to apply garlic as insecticide and larvicide to control infestation. The study aimed to investigate the effect of garlic extract towards the mortality of blowfly’s larvae and effective concentrations using LC50 and LC90. Ten blowfly larvae were used for each of these concentrations: 0.5%, 1%, 2%, 4%, with negative control of 5 repetitions, observed every 6 hours within 2x24 hours. The Kruskal-Wallis test result showed a Sig value of 0.0010.05, while Spearman analysis found Sig value of 0.0010.025, which meant that there was a significant effect of increasing garlic extract concentration toward blowfly larvae mortality. Mann-Whitney test found Sig value of 0.0010.05. Probit analysis showed LC50 and LC90 values were at 2.701% and 5.498% concentrations. 4% concentration caused the most larvae mortality. It is suggested to use garlic liquid extract to control blowflies.